A case report of Multiple Symmetric Lipomatosis (MSL) in an East Asian Female - Kyunghun Jung; Soonchul Lee (BMC, 2020)
Abstract Background Multiple Symmetric Lipomatosis (MSL) is a rare disorder related to fat metabolism and lipid storage. The condition results in characteristic depositions of fat, especially around the cephalic, cervical, and upper thoracic subcutaneous. It is much more common in adult males who live in the Mediterranean region and has only rarely been reported in Asian females. In this report, we present a case of an Asian female with MSL and also review the clinical features of the condition, including radiological and histological findings required for proper diagnosis and management. Case presentation A 59-year-old Korean female came in with a chief complaint of palpable mass present in shoulder and upper back regions. Images showed diffuse non-encapsulated adipose tissue in the subcutaneous layer of the suboccipital, posterior neck area. The patient wanted to remove the mass for cosmetic reasons and discomfort. Excisional biopsy was planned. Preoperative blood analyses showed deteriorated liver function, and the computed tomography findings were consistent with liver cirrhosis. Detailed history taking revealed that she consumed highly levels of alcohol. Lipectomy was performed and the histological findings demonstrated large dystrophic adipocyte morphology. The patient was recovered uneventfully. Conclusion When patients have multiple symmetric lipomatous lesions, clinicians should suspect MSL and survey possible associated conditions, such as alcoholism, liver cirrhosis, dyspnea, and neuropathy in detail.